2021
DOI: 10.3390/ijerph18073464
|View full text |Cite
|
Sign up to set email alerts
|

Oral Health Status, Knowledge, and Behaviours of People with Diabetes in Sydney, Australia

Abstract: This study assessed self-reported oral health status, knowledge, and behaviours of people living with diabetes along with barriers and facilitators in accessing dental care. A cross sectional survey of 260 patients from four public diabetes clinics in Sydney, Australia was undertaken using a 35-item questionnaire. Data were analysed using SPSS software with descriptive and logistic regression analyses. More than half (53.1%) of respondents reported having dental problems which negatively impacted their related… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
25
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 18 publications
(27 citation statements)
references
References 36 publications
1
25
1
Order By: Relevance
“…These are very positive findings that could be attributed to the way the items were developed. The first item explored the most common dental problems linked with poor oral health, and more than half of the respondents reported (53%) these concerns (dry mouth, gaps between teeth, pain in teeth and/or gums and loose teeth) in the related study surveying people with diabetes in Australia [ 38 ]. The second item related to the frequency of dental visits in the last 12 months as the evidence shows that infrequent dental attendance is associated with poor oral health [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…These are very positive findings that could be attributed to the way the items were developed. The first item explored the most common dental problems linked with poor oral health, and more than half of the respondents reported (53%) these concerns (dry mouth, gaps between teeth, pain in teeth and/or gums and loose teeth) in the related study surveying people with diabetes in Australia [ 38 ]. The second item related to the frequency of dental visits in the last 12 months as the evidence shows that infrequent dental attendance is associated with poor oral health [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…A meta-analysis 23 studies of analysing diagnostic accuracy found that specificity significantly reduced with higher prevalence [ 56 ]. These findings are relevant to the current study as there is a high prevalence of dental problems among people with diabetes ranging from 53–86% depending on the demographic profile [ 38 , 57 , 58 ]. Low specificity and NPV is an issue for screening tools if there are cost implications or risk of harm and discomfort to the patient from treatment [ 53 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations